Effectiveness of Jigsaw-Flash Learning Model in Geometry Material - Imam Pakhrurrozi; Imam Sujadi; Ikrar Pramudya (International Journal of Science and Applied Science: Conference Series, 2017)
This study aims to determine and describe the effectiveness of the use of jigsaw-flash learning model on geometry material. The jigsaw-flash learning model is a jigsaw learning model which is modified with adobe flash media. The research method used is mix method research with exploratory sequential strategy. This research was conducted in state junior high schools in Surakarta. Subjects in this study were the students of class VIII namely class VIII-2 as an experimental class and class VIII-3 as a control class selected by random sampling technique. The experimental class was taught with a jigsaw-flash learning model and the control class was taught with a jigsaw model. The procedures performed in this study include qualitative data collection and data analysis followed by quantitative data collection and data analysis. The researcher used interview method for collecting qualitative data. While quantitative data collection was conducted by test and the analysis technique used was t-test. The results of this study indicate that students feel more comfortable and interested in studying geometry material taught by jigsaw-flash model. In addition, students taught using the jigsaw-flash model are more active and motivated than the students who were taught using jigsaw models in studying geometric material. This shows that the use of the jigsaw-flash model can increase student participation and motivation. The results of this study also indicate that the increase in student achievement taught by the jigsaw-flash model which is indicated by t-test result t = 2,259 with df = 38. Based on the results, it can be concluded that jigsaw-flash model is more effective than jigsaw model. Therefore, teachers need to consider the use of jigsaw-flash learning model in learning geometry material.